2023
DOI: 10.1149/2162-8777/ad0888
|View full text |Cite
|
Sign up to set email alerts
|

Editors’ Choice—Structural, Electrical, and Luminescent Properties of Orthorhombic κ-Ga2O3 Grown by Epitaxial Lateral Overgrowth

V. I. Nikolaev,
A. Y. Polyakov,
A. V. Myasoedov
et al.

Abstract: The properties of orthorhombic κ-Ga2O3 films grown by Epitaxial Lateral Overgrowth (ELOG) were studied by Scanning Transmission Electron Microscopy (STEM), X-ray diffraction, capacitance-voltage profiling, Microcathodoluminescence (MCL) spectroscopy and imaging. ELOG mask was formed by deposition of SiO2 stripes on TiO2 buffer prepared on basal plane sapphire, with the stripes going along the [11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In previous studies, the kand e-Ga 2 O 3 have mainly been observed in the films epitaxially grown on a-Al 2 O 3 (0 0 1) (c-cut sapphire) substrates, 7,9,20,25,31,41,[45][46][47][48] whereas only in a few cases have the substrate temperatures below 500 1C been sufficient for formation of these phases. 25,48 Moreover, a relatively complex method, that is, epitaxial lateral overgrowth, including the deposition of the TiO 2 seed layer on c-sapphire and a following lithography process to form a pattern that supports the k-Ga 2 O 3 growth, has been developed 53 and applied 54 for improving the quality of k/e-Ga 2 O 3 films. However, even in these cases, substrate temperatures of 540-570 1C have been used for deposition of the films by halide vapour phase epitaxy.…”
Section: Phase Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the kand e-Ga 2 O 3 have mainly been observed in the films epitaxially grown on a-Al 2 O 3 (0 0 1) (c-cut sapphire) substrates, 7,9,20,25,31,41,[45][46][47][48] whereas only in a few cases have the substrate temperatures below 500 1C been sufficient for formation of these phases. 25,48 Moreover, a relatively complex method, that is, epitaxial lateral overgrowth, including the deposition of the TiO 2 seed layer on c-sapphire and a following lithography process to form a pattern that supports the k-Ga 2 O 3 growth, has been developed 53 and applied 54 for improving the quality of k/e-Ga 2 O 3 films. However, even in these cases, substrate temperatures of 540-570 1C have been used for deposition of the films by halide vapour phase epitaxy.…”
Section: Phase Compositionmentioning
confidence: 99%
“…However, even in these cases, substrate temperatures of 540-570 1C have been used for deposition of the films by halide vapour phase epitaxy. 53,54 Hence, the thermal ALD based on GaI 3 and O 3 provides a much simpler approach for deposition of films containing k-Ga 2 O 3 .…”
Section: Phase Compositionmentioning
confidence: 99%